Geopolitics of Tourism and Academia in the Holy Land. Issue 3 (3rd July 2017) - Ram, Yael; Isaac, Rami K.; Shamir, Omri; Burns, Peter
ABSTRACT: The premise for this paper is that tourism scholars researching in Israel and Palestine are, in effect, actors in the geopolitical landscape of the Holy Land. Political tourism is a significant factor in how the Israel–Palestine geopolitical conflict is represented. The current paper provides an analysis of how tourism academics address the situation. A research team of Israeli, Palestinian and a third country origins collaborated to produce a narrative synthesis by systematically reviewing 35 academic papers selected through defined criteria. This approach minimized bias and aimed for analytical robustness and validity. Two main conclusions are derived from the analysis. First, papers tend to focus on the social, touristic and religious aspects of tourism not on the core issues of the geopolitical conflict. Second, the works did not contribute to dialogue between parties but reinforced separateness thus reflecting the political conflict.